Towards a Neurophysiological Approach of Managing Sport-Originated Brain Injury - McGeown, Joshua Patrick (Auckland University of Technology, 2021)
Of the estimated 27 million traumatic brain injuries (TBIs) annually, 95% are considered mild TBIs (mTBIs), that are not life threatening but lead to disturbances in normal brain function. While these injuries are described as “mild” a considerable proportion of patients suffer mTBI-related symptom burden for weeks, months, and in some cases years post-injury. The number of patients suffering from persistent mTBI-related complications, and the cost for healthcare systems, indicates a need to advance the clinical management of these injuries. Approximately one fifth of TBIs result from a sport/physical activity related mechanism of injury, with 98% of these sport-originated brain injuries (SOBI) considered to be mTBI. SOBI is a problem for clinicians who manage athletes with these injuries. The advances in our understanding of the neurophysiological consequences of TBI provide targets for novel assessments and interventions to improve clinical outcomes. Considerable gaps exist in current clinical management pathways that contribute to poor recovery outcomes and prolonged burden. These gaps range from needing to understand which clinical factors contribute to variability in recovery outcomes, identifying objective measurements that can feasibly assist clinicians who work with mTBI patients, and innovative methods to proactively reduce the damaging neurophysiological consequences of brain injury. Many mTBI researchers focus their effort in a specific subdiscipline to gain intimate knowledge of a specific aspect of mTBI. However, holistic research efforts are needed to link the findings of these endeavours to translate this knowledge to the benefit of mTBI patients. This PhD aimed to evaluate how a diverse collection of evolving neurophysiological approaches to assessing and managing mTBI might translate from bench to bedside for SOBI. The two main research questions were “what factors influence time to recovery following SOBI?“ and “what is the translational potential of neurophysiological approaches to advance clinical management of SOBI?”. The purpose of structuring the thesis into two sections was to develop a diverse technical skillset and multidisciplinary understanding of what is required to improve translation of promising findings from highly controlled studies into real-world clinical environments. The methodological approach to this thesis was to conduct embedded quantitative research within a functioning clinical SOBI service. The design, analysis, and interpretation of studies that were not clinically embedded prioritised ecological validity of findings. Overall, this thesis presents a case study, systematic review, cross-sectional study, experimental study, and multiple cohort studies (both retrospective and prospective). There were consequences caused by suboptimal clinical assessment protocols as reported in our case study of an individual with a history of SOBI experiencing prolonged symptoms. Using retrospective analysis of SOBI clinic data, predictors of SOBI recovery trajectories were identified. Insufficiencies in clinical pathways were the greatest modifiable factor that influenced recovery outcomes post-SOBI. Identification of subgroups of SOBI patients based on their predominant symptom cluster was a key factor related to recovery. Patients with vestibulo-ocular symptomology were particularly vulnerable to negative outcomes. Therefore, education and training of clinicians so they can recognise and treat these symptom profiles more effectively is needed. Figures claiming the majority of SOBI patients will be recovered by 14-days post-injury are out of date and require updating given our study showed that closer to 50% of patients experienced symptoms beyond this timeframe. Our systematic review of experimental literature evaluating the effect of nutritional interventions to improve neurophysiological outcomes of TBI identified that anti-oxidant, branched chain amino acid, and ω-3 polyunsaturated fatty acid supplementation appear to be the most promising candidates to proactively lessen brain damage and burden caused by TBI. Since the biofidelity of the animal studies was low and no studies have evaluated nutritional interventions on neurophysiological outcomes in humans, a feasibility study would be necessary before dedicating time and resources to a clinical trial. The translational potential and clinical utility of neurophysiological based assessments to provide objective data to assist clinical decision making and enable the evaluation of a nutritional intervention to improve SOBI recovery outcomes were evaluated. Clinical utility of somatosensory assessments to assist clinicians working with SOBI patients when making diagnostic decisions, predicting recovery trajectories, and determining if neurophysiological recovery coincided with clinical recovery was assessed. Machine learning was used to develop an algorithm using wearable sensor data acquired during an incremental stress test to classify mTBI symptom subclusters. Brain-derived neurotrophic factor (BDNF), a biomarker of neuroplasticity, was measured non-invasively within saliva under clinically realistic conditions to begin to understand the relationships between BDNF and symptom burden. Several methodological issues that are likely to prevent the translational of neurophysiological approaches to the benefit of current clinical practice in the future were identified. Neither salivary-BDNF or somatosensory assessments appear to offer utility to improve clinical assessment of SOBI, nor to evaluate the potential benefit of a nutritional intervention. The potential value of using wearable sensors and machine learning algorithms to collect and analyse objective data during an already established clinical test was the most promising finding but requires a great amount of development. Overall, the evidence did not suggest that nutritional interventions or neurophysiological assessments will be coming to the aid of clinicians and their SOBI patients soon. Future studies need to prioritise study designs that emphasise biofidelity and ecological validity so that findings are more likely to translate to clinical practice. In the interim, responsibility falls on healthcare organisations, educational institutes, and sporting bodies to improve the education, standards, and pathways moving forward to reduce the burden caused by persistent complications following SOBI.
Keywords: Brain injury; Concussion; Neurorehabilitation; Sports injuries; Clinical science; Translational science